Encyclopaedia universalis (Encyclopaedia Universalis France S.A.)
Exemplares nÇ 0015187, 0015186, 0015185 e 0015190 em depósito / caixa 285. - Exemplares nÇ 0015189, 0015188, 0015193 e 0015192 em depósito / caixa 286. - Exemplares nÇ 0015191, 0015195, 0015194 e 0015198 em depósito / caixa 287. - Exemplares nÇ 0015197, 0015196, 0015201 e 0015200 em depósito / caixa 288. - Exemplares nÇ 0015199, 0015205, 0015204, 0015203 e 0015202 em depósito / caixa 289